Digital Transformation in Administrative and Learning Management at MTs Muallimin Univa Medan in the Society 5.0 Era - Aulia, Ainun Meryna; Siahaan, Amiruddin (El-Idare: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the implementation of digital transformation in administrative and learning management at MTs. Muallimin UNIVA Medan in the Society 5.0 era. The research is motivated by the limited study of digital transformation that integrates aspects of administration, learning, human resource readiness, and Islamic education values comprehensively in the madrasah environment. The research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The research informants consist of madrasah heads, deputy madrasah heads, teachers, administrative staff, and students who are directly involved in the implementation of education digitalization. The results of the study show that digital transformation at MTs. Muallimin UNIVA Medan has had a positive impact on the quality of education, especially in improving learning effectiveness, administrative efficiency, and digital literacy of students and teachers. The use of digital media, online learning platforms, and the use of EMIS and Madrasah Digital Report Cards help accelerate data management and create more interactive learning. However, the implementation of digital transformation still faces several obstacles, such as limited technology infrastructure, a gap in teachers' digital competencies, and the lack of a comprehensive administrative system. This study concludes that the success of digital transformation requires policy support, readiness of human resources, technological infrastructure, collaborative culture, and integration of Islamic education values so that digitalization can run optimally and sustainably.